DNA Methylation of the Natriuretic Peptide System Genes and Ischemic Stroke: Gene-Based and Gene Set Analyses. (11th June 2022) - Peng, Hao; Fan, Yiming; Li, Jing; Zheng, Xiaowei; Zhong, Chongke; Zhu, Zhengbao; He, Yan; Zhang, Mingzhi; Zhang, Yonghong
Abstract : Background and Objectives: The natriuretic peptide (NP) system has been considered an important regulator for ischemic stroke (IS) with a limited clinical implication. A better understanding of the underlying molecular mechanisms is urgent. Here, we aimed to examine the role of DNA methylation of NP system genes in IS. Methods: DNA methylation at promoter regions of 4 core NP system genes, e.g., CORIN, FURIN, NPPA, and NPPB, was measured by targeted bisulfite sequencing in 853 patients with IS and 918 controls. We first examined the association between DNA methylation at each single CpG and IS, followed by gene-based and gene set analyses to examine the joint associations of DNA methylation at multiple CpGs in a gene or all 4 genes as a pathway with IS. Results: After control of covariates and multiple testing, DNA methylation at 19 of the 36 assayed CpGs was individually associated with IS at q < 0.05. Higher average methylation levels at the targeted regions of CORIN (odds ratio [OR] = 0.64, 95% confidence interval [CI]: 0.56–0.73), FURIN (OR = 0.78, 95% CI: 0.69–0.88), and NPPA (OR = 0.78, 95% CI: 0.69–0.88) were associated with a lower odds of IS (all q < 0.05). The truncated product method revealed the same gene-based associations (all q < 0.05) and found that DNA methylation at all 4 NP system genes together was jointly associated with IS ( p = 0.0001). Discussion: DNA methylation at NP system genes was downregulated in patients with IS. Our results may unravel a molecular mechanism underlying the regulating effect of the NP system on IS and highlight the relevance of testing the joint effect of multiple CpGs in the epigenetic analysis.